Genetic labeling of the nucleus of tractus solitarius neurons associated with electrical stimulation of the cervical or auricular vagus nerve in mice - Md Sams Sazzad Ali; Ghazaal Parastooei; Swarnalakshmi Raman; Jalen Mack; Yu Shin Kim; Man-Kyo Chung (Brain Stimulation, 2024)
Introduction: Vagus nerve stimulation (VNS) is clinically useful for treating epilepsy, depression, and chronic pain. Currently, cervical VNS (cVNS) treatment is well-established, while auricular VNS (aVNS) is under development. Vagal stimulation regulates functions in diverse brain regions; therefore, it is critical to better understand how electrically-evoked vagal inputs following cVNS and aVNS engage with different brain regions. Objective: As vagus inputs are predominantly transmitted to the nucleus of tractus solitarius (NTS), we directly compared the activation of NTS neurons by cVNS or aVNS and the brain regions directly projected by the activated NTS neurons in mice. Methods: We adopted the targeted recombination in active populations method, which allows for the activity-dependent, tamoxifen-inducible expression of mCherry—a reporter protein—in neurons specifically associated with cVNS or aVNS. Results: cVNS and aVNS induced comparable bilateral mCherry expressions in neurons within the NTS, especially in its caudal section (cNTS). However, the numbers of mCherry-expressing neurons within different subdivisions of cNTS was distinctive. In both cVNS and aVNS, anterogradely labeled mCherry-expressing axonal terminals were similarly observed across different areas of the forebrain, midbrain, and hindbrain. These terminals were enriched in the rostral ventromedial medulla, parabrachial nucleus, periaqueductal gray, thalamic nuclei, central amygdala, and the hypothalamus. Sex difference of cVNS- and aVNS-induced labeling of NTS neurons was modest. Conclusion: The central projections of mCherry-expressing cNTS terminals are comparable between aVNS and cVNS, suggesting that cVNS and aVNS activate distinct but largely overlapping projections into the brain through the cNTS.